Principles of Diabetes Mellitus - Poretsky, Leonid; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Principles of Diabetes Mellitus, Second Edition is an important update to the comprehensive textbook first published in 2002 and reissued in 2004. It is written for physicians of all specialties who, on a daily basis, deal with an illness which has reached epidemic proportions. The book is also intended for medical students and investigators of all aspects of diabetes. The last five years have witnessed major developments in our understanding of diabetes and in therapeutic approaches to this disease. Thus, in addition to updating all chapters, the authors added eight new chapters to the second edition. Principles of Diabetes Mellitus, Second Edition covers diabetes in all of its aspects—genetics, epidemiology, pathophysiology, clinical manifestations, therapy and prevention.
I -- The Main Events in the History of Diabetes Mellitus -- II. Physiology of glucose metabolism -- Normal Glucose Homeostasis -- Endocrine Pancreas -- The Role of Incretins in Insulin Secretion -- Cellular Mechanisms of Insulin Action -- The Role of Brain in Glucose Metabolism -- III. Diagnosis and epidemiology of diabetes -- Diagnostic Criteria and Classification of Diabetes -- Epidemiology -- Diabetes in Culturally Diverse Populations: From Biology to Culture -- IV. Genes and diabetes -- Genetics of Type 2 Diabetes: From Candidate Genes to Genome-Wide Association Analysis -- Rodent Models of Diabetes -- V – Diabetes Syndromes -- Type 1 Diabetes Mellitus: Epidemiology, Genetics, Pathogenesis, and Clinical Manifestations -- Type 2 Diabetes Mellitus: Epidemiology, Genetics, Pathogenesis, and Clinical Manifestations -- Maturity-Onset Diabetes of the Young: Molecular Genetics, Clinical Manifestations, and Therapy -- Diabetes in Pregnancy -- Secondary Causes of Diabetes Mellitus -- Syndromes of Extreme Insulin Resistance -- VI. Complications of diabetes -- Acute Hyperglycemic Syndromes: Diabetic Ketoacidosis and the Hyperosmolar State -- Hypoglycemia in Diabetes Mellitus -- Intake of Advanced Glycation Endproducts: Role in the Development of Diabetic Complications -- Diabetic Retinopathy -- Diabetic Nephropathy -- Diabetic Neuropathy -- Peripheral Vascular Disease in Diabetes -- The Diabetic Foot -- Male Sexual Dysfunction in Diabetes Mellitus -- Gastrointestinal Manifestations of Diabetes -- Dyslipidemia: Pathogenesis and Management -- Dermatological Complications of Diabetes Mellitus; Allergy to Insulin and Oral Agents -- VII. Related disorders -- Obesity – Genetics, Pathogenesis, Therapy -- Hypertension -- Coronary Artery Disease and Cardiomyopathy -- Polycystic Ovary Syndrome -- Insulin Resistance and the Metabolic Syndrome -- Diabetes and Liver Disease -- The Increased Risk of Cancer in Obesity and Type 2 Diabetes: Potential Mechanisms -- Diabetes and Sleep Disorders -- HIV Infection and Diabetes -- VIII. Therapy of diabetes mellitus—general principles -- Glycemic Goals -- Behavioral and Educational Approaches to Diabetes Self-Management -- Dietary Therapy of Diabetes Mellitus -- Exercise in the Therapy of Diabetes Mellitus -- Therapy of Type 1 Diabetes Mellitus -- Treating Type 2 Diabetes Mellitus -- Prevention of Microvascular Complications of Diabetes – General Overview -- Psychiatric Care of the Patient with Diabetes -- Management of Diabetes and Hyperglycemia in the Hospital Setting -- The Future of Diabetes Therapy -- IX – Diabetes prevention -- Prevention of Type 1 Diabetes Mellitus -- Prevention of Type 2 Diabetes Mellitus -- X -- Resources for Patients with Diabetes.
Keywords: Diabetes; Endocrinology .; Primary care (Medicine).; Cardiology; Diabetes; Endocrinology; Primary Care Medicine; Cardiology